MODEL GRAVITASI PERDAGANGAN EKSPOR KARET INDONESIA KE AMERIKA SERIKAT - Yanita, Mirawati; HD, Ernawati; Elwamendri (AGRIPITA JOURNAL, 2018)
Indonesia is the second rubber producing country in the world after Thailand, faces more intense competition with the other rubber exporting countries, such as Vietnam, India and China. The United States of America is the main destination for Indonesian rubber exports. Despite fluctuations in the number of exports, especially the decline in exports in all countries due to the global crisis in 2009, until 2015 the average Indonesian exports increased. The paper objective is examining the determination of Indonesian rubber exports to the main export destination country. By using secondary data in the Gravity model it is found that the variables of GDP, total exports and boundaries have a significant influence. There is a negative relationship between distance and population size in the flow of trade. In the future Indonesia needs to diversify its rubber export destination and qualification to countries that still experience under and overtraded conditions.